Spinal Anaesthesia Failure among Women Undergoing Caesarean Section in Kirtipur Hospital - Rajbhandari, PK; Pradhan, P; Dangal, G (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study was done to find out the spinal anaesthesia failure rate necessitating the conversion to general anaesthesia and use of intraoperative supplemental analgesia. Methods: This was a retrospective study undertaken in Kirtipur hospital in 660 patients. Spinal anaesthesia (0.5% heavy bupivacaine 2.2 ml) was given to women who had undergone elective or emergency caesarean section from January 2009 to December 2013. Results: In this study spinal anaesthesia failure rate was 1.66% (n=11/660). Among them complete failed spinal anaesthesia rate was 0.75% (n=5/660) requiring conversion to general anaesthesia. Intraoperative supplemental analgesic and sedation like pethidine, ketamine or midazolam was required in 0.90% (n=6/660). Conclusions: The failure rate of spinal anaesthesia given for caesarean section was low (1.66%) and it was within the acceptable range.